Propuesta De Diseño De Un Modelo De Techos Verdes Para La Universidad Antonio Nariño, Sede Sur - Bogotá - Mendez Rozo, María Victoria (Universidad Antonio Nariño, 2021)
Surrounds block 5 of south headquarters Antonio Nariño University (UAN) is the problem of noise. It exceeds the 65db permitted established in resolution 0627 of 2006 issued by the Ministry of Environment. So, the objective of this research is to make a design proposal for a green roof model for those facilities as an alternative to mitigate this problem. The methodology consists of gathering information to generate a diagnosis of the place. Firstly, a technical evaluation for the green roof construction and a cost-benefit analysis is made. Secondly, a procedure is developed for the implementation of the proposal. It has been identified that the most suitable green roof technique is an extensive and self-regulated ecological classification roof, with a monolithic multilayer technology. From the application of the approach used for this project and following the guidelines used in the literature, it is achieved to consider an extensive green roof proposal for south headquarters Antonio Nariño University which mitigates the problem of noise and generates additional benefits such as temperature management, improvement in air quality, water resource management, potential energy savings, certifications for sustainable construction, generation of well-being for the community, among others.